The pros and cons of teaching large classes: the Zimbabwean primary school experience - Ndlovu, Emily; Mangwaya, Ezron (2016)
Oftentimes large classes are associated with ineffective teaching and learning. This qualitative study explores how four Zimbabwean primary school teachers handled classes of more than 60 learners. Using two English lessons, one Environmental Science lesson and one Religious and Moral Education lesson the study explores strategies that can be utilised to teach large classes in developing countries. While the study acknowledges the merits of teaching small classes, it however, observes that the phenomenon of large classes is likely to be an enduring feature for developing countries, including Zimbabwe. The four lessons taught by primary school teachers are not perfect but they do provide a basis for seriously considering adopting strategies that enhance the teaching of large classes.